EMPLOYEE PRESENCE APPLICATION USING SWAFOTO AND LOCATION BASED SERVICE AT THE FACULTY OF SCIENCE AND TECHNOLOGY AT UNIVERSITAS TERBUKA - Dian Nurdiana; Andri Suryadi (Informatika, Universitas Jenderal Soedirman, 2022)
The Covid-19 pandemic gave birth to a policy of limiting employees who work from office (WFO) and employees who work from home (WFH). At the Faculty of Science and Technology (FST) of the Universitas Terbuka, attendance for employees who do WFH uses Microsoft Form. This is considered impractical and raises several problems. This study will develop a presence application by utilizing selfies and location-based services based on Android. The purpose of this study is to assist in processing attendance data by knowing the location of the employee and authentication using the employee's face. The system can process data into reports that can help faculty know the activities and performance of employees. The software development methodology uses Agile Development. This model has stages including planning, design, develop, test, release, and planning stages. Each stage in the Agile Development model is carried out in an organized and structured manner according to agreed rules and solutions. Software testing uses Black Box Testing which will test the functions, inputs, and outputs of software or applications based on needs. There are 20 test scenarios performed for users and administrators. From testing using Black Box Testing, 100% of the functions run well, so it can be concluded that the application is suitable for use in the Faculty of Science and Technology of the Universitas Terbuka.